2023
DOI: 10.3390/ijms24043161
|View full text |Cite
|
Sign up to set email alerts
|

Targeting and Monitoring Acute Myeloid Leukaemia with Nucleophosmin-1 (NPM1) Mutation

Abstract: Mutations in NPM1, also known as nucleophosmin-1, B23, NO38, or numatrin, are seen in approximately one-third of patients with acute myeloid leukaemia (AML). A plethora of treatment strategies have been studied to determine the best possible approach to curing NPM1-mutated AML. Here, we introduce the structure and function of NPM1 and describe the application of minimal residual disease (MRD) monitoring using molecular methods by means of quantitative polymerase chain reaction (qPCR), droplet digital PCR (ddPC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 166 publications
0
4
0
Order By: Relevance
“…Patients with CMML carrying the NPM1 mutation presented at a relatively young age, with a median of 60 years (range, . This subgroup exhibited distinctive characteristics, including a median bone marrow blast count of 13% (10)(11)(12)(13)(14)(15)(16)(17)(18)(19), leukocytes of 15.7 × 10 9 (12.24-30.6), a platelet count of 98 × 10 9 (35-110), and a median hemoglobin concentration of 85 g/L (49-138). Among these five patients, three were eligible for intensive chemotherapy and attained a complete response with a significant reduction in NPM1 ratio.…”
Section: Seven Additional Cases Of Unusual Presentation Of Npm1mut Mnmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients with CMML carrying the NPM1 mutation presented at a relatively young age, with a median of 60 years (range, . This subgroup exhibited distinctive characteristics, including a median bone marrow blast count of 13% (10)(11)(12)(13)(14)(15)(16)(17)(18)(19), leukocytes of 15.7 × 10 9 (12.24-30.6), a platelet count of 98 × 10 9 (35-110), and a median hemoglobin concentration of 85 g/L (49-138). Among these five patients, three were eligible for intensive chemotherapy and attained a complete response with a significant reduction in NPM1 ratio.…”
Section: Seven Additional Cases Of Unusual Presentation Of Npm1mut Mnmentioning
confidence: 99%
“…Finally, various NPM1-targeted approaches such as menin inhibitors and FLT3 kinase inhibitors are under investigation with promising results [10,33], which warrants the identification of this potential druggable candidate in all patients with a myeloid malignancy [16].…”
Section: Review 41 Npm1 In Leukemogenesis and Its Clinical Impactmentioning
confidence: 99%
See 1 more Smart Citation
“…We have shown that these combinations can increase antigenspecific immune responses against leukemic cells as well as LPC/LSC [82,83]. Image generated using information from the following articles [5][6][7][8]27,39,41,47,55,56,[64][65][66][67][68][69][70][71]80,[83][84][85][86][87][88].…”
Section: Figure 2 Combinations Of Immunotherapeutic Treatments Can Us...mentioning
confidence: 99%
“…The potential of VISTA blockade as an immunotherapeutic strategy against AML with the aim of boosting antitumor immune responses and modulating the inflammatory microenvironment is discussed. Furthermore, our contributing authors provide comprehensive reviews concerning the impact of mutations or dysregulation of key proteins such as TET proteins [ 5 ], IKAROS [ 6 ], S100A8/9 [ 7 ], NPM1 [ 8 ], and RasGRP [ 9 ] on hematologic malignancies, along with potential therapeutic strategies targeting these molecules for diagnosis and treatment. Another review addresses metabolic reprogramming in lymphomas, exploring potential signaling pathways driving these alterations and discussing therapeutic strategies targeting metabolic pathways [ 10 ].…”
mentioning
confidence: 99%